The cocrystal rac‐1‐[(N, 4‐dimethylbenzenesulfonamido)methyl]‐2‐(diphenylphosphoryl)ferrocene–rac‐1‐[(N, 4‐dimethylbenzenesulfonamido)methyl]‐2‐(diphenylphosphanyl)ferrocene (0.45/0.55). Issue 3 (22nd February 2014) - Wei, Muh‐Mei; Audin, Catherine; Manoury, Eric; Deydier, Eric; Daran, Jean‐Claude
<x xml:space="preserve">Abstract</x> As part of our interest in the synthesis and catalytic applications of chiral (diphenylphosphanyl)ferrocene ligands, we designed a number of P, N‐containing ligands for use in asymmetric transfer hydrogenation (ATH). During the synthetic procedure to obtain rac‐1‐[(N, 4‐dimethylbenzenesulfonamido)methyl]‐2‐(diphenylphosphanyl)ferrocene, the title compound, [Fe(C5H5)(C26H25NO2PS)]0.55·[Fe(C5H5)(C26H25NO3PS)]0.45, was obtained as a by‐product. It is composed of a ferrocene group disubstituted by a partially oxidized diphenylphosphanyl group, as confirmed by 31P NMR analysis, and an (N, 4‐dimethylbenzenesulfonamido)methyl substituent. Owing to the partially oxidized diphenylphosphanyl group, it is best to view the crystal as being composed of a mixture of non‐oxidized and oxidized phosphane, so it can be regarded as a cocrystal. It is also a racemate. To the best of our knowledge, the P=O distance [1.344 (4) Å] is the shortest observed for related (diphenylphosphoryl)ferrocene compounds. The packing is stabilized by weak C—H...O interactions, forming R22(10) hydrogen‐bonding motifs, which build up a chain along the c axis.